c-Myc-Induced Extrachromosomal Elements Carry Active Chromatin - Smith, Greg (Neoplasia Press Inc., 2003)
Murine Pre-B lymphocytes with experimentally activated MycER show both chromosomal and extrachromosomal gene amplification. In this report, we have elucidated the size, structure, and functional components of c-Myc-induced extrachromosomal elements (EEs). Scanning electron microscopy revealed that EEs isolated from MycER-activated Pre-B+ cells are an average of 10 times larger than EEs isolated from non-MycER-activated control Pre-B- cells. We demonstrate that these large c-Myc-induced EEs are associated with histone proteins, whereas EEs of non-MycER-activated Pre B- cells are not. Immunohistochemistry and Western blot analyses using pan-histone-specific, histone H3 phosphorylation-specific, and histone H4 acetylation-specific antibodies indicate that a significant proportion of EEs analyzed from MycER-activated cells harbors transcriptionally competent and/or active chromatin. Moreover, these large, c-Myc-induced EEs carry genes. Whereas the total genetic make-up of these c-Myc-induced EEs is unknown, we found that 30.2% of them contain the dihydrofolate reductase (DHFR) gene, whereas cyclin C (CCNC) was absent. In addition, 50% of these c-Myc-activated Pre-B+ EEs incorporated bromodeoxyuridine (BrdU), identifying them as genetic structures that self-propagate. In contrast, EEs isolated from non-Myc-activated cells neither carry the DHFR gene nor incorporate BrdU, suggesting that c-Myc deregulation generates a new class of EEs.